Late-Onset Myocarditis Following Immune Checkpoint Inhibitors Therapy: A Case Series with Literature Review - Harun Muğlu; Erdem Sünger; Bahadır Köylü; Didem Tunalı; Cengiz Erol; Fatih Selcukbiricik; Ahmet Bilici; Omer Fatih Olmez (Medicina, 2025)
Immune checkpoint inhibitors (ICIs) therapy has revolutionized cancer treatment. However, it is important to acknowledge that ICI therapy can lead to immune-related adverse events (irAEs), including myocarditis. While early-onset myocarditis is well-documented, late-onset cases are increasingly recognized. This case series presents four cases of late-onset ICI-associated myocarditis, emphasizing the need for long-term surveillance of this potentially fatal complication. Patients exhibited a range of cardiac symptoms, including chest pain, shortness of breath, and arrhythmias. The diagnosis was confirmed through cardiac magnetic resonance imaging (MRI) and elevated cardiac biomarkers. Treatment involved the immediate discontinuation of ICI therapy and the initiation of high-dose corticosteroids. In cases with an inadequate response, additional immunosuppressive agents were considered. This case series underscores the importance of prolonged monitoring for late-onset ICI-associated myocarditis. Further research is needed to establish optimal treatment strategies and long-term management approaches for this complex condition.